Conceptual Design of a 10-Seater Electric Aircraft - A Marcell; Frentsen Limor; J F Humairah; M D T Z Baniz; Taufiq Mulyanto (Institut Teknologi Bandung, 2022)
With the increase in population, an increase of transportation needs is inevitable, especially in air travel. There is an underlying problem in this matter that is carbon pollutions. Air travel contributes around 2% of the global emissions. This paper contains the conceptual design of 10-seater electric aircraft that can serve as a cleaner alternative for air travel. The paper will discuss about our objectives and the results of configurations, backed with calculations of proof in all aspects that is needed. In conclusions, this paper presents a conceptual design of 10-seater electric aircraft that have range more than 450 km. The aircraft being designed has a mid-wing three surface configuration with a MTOW of 7250 kg.